2019
DOI: 10.7903/cmr.19268
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Continuance to Share Location on Social Networking Sites: The Influence of Privacy Concern, Trust, Benefit and the Moderating Role of Positive Feedback and Perceived Promotion Innovativeness

Abstract: Location sharing has become an indispensable part of social networking sites (SNSs) that brings business many opportunities and fosters sustainable business activities by increasing the efficiency of location promotion. This study investigated the factors that affect location sharing behavior among SNS users and how to sustain such behavior. The results of our survey of 210 Facebook users recruited from MTurk indicated that privacy concerns and trust in SNS members have significant impacts on the perceived ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…The finding also confirms that incentives is the primary driver which determines Malaysian consumers' continuance intention and continuance use of a mobile shopping app. Once consumers realise that the incentives offered by mobile shopping apps increase the value of their purchases, they are more likely to have a continuance intention using them (Chen & Ha, 2019;Chopdar& Balakrishnan, 2020). Besides, Cheng et al (2022) claimed that incentives make it difficult for consumers to resist the temptation to buy, thus it is not surprising that incentives are the main reason driving continuance intention (Tamara et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding also confirms that incentives is the primary driver which determines Malaysian consumers' continuance intention and continuance use of a mobile shopping app. Once consumers realise that the incentives offered by mobile shopping apps increase the value of their purchases, they are more likely to have a continuance intention using them (Chen & Ha, 2019;Chopdar& Balakrishnan, 2020). Besides, Cheng et al (2022) claimed that incentives make it difficult for consumers to resist the temptation to buy, thus it is not surprising that incentives are the main reason driving continuance intention (Tamara et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Incentives refer to the rewards given to participants who participate in an activity (Chen & Ha, 2019). According to Bøe et al (2021), incentives can be in monetary or non-monetary form.…”
Section: Incentive and Continuance Intentionmentioning
confidence: 99%
“…The study revealed that there is a significant and positive relationship between organization and continuance usage (H4). This indicates that the organizational variables just-in-time delivery, creativity, efficiency, innovations, and leadership [ 51 ] influences the continuance usage of drone technologies in healthcare delivery. In terms of organizational issues, [ 87 ] opine that critical consideration be given when implementing large and complex information systems and technology, particularly in regard to top management support and facilitating conditions for the information systems and technology development within medical environments.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of smart services is linked to the discomfort experienced by users who utilize SCS technology. Users’ dissatisfaction is likely to have a negative impact on their capacity to use the channels, as well as on their perceptions of SCS in general [ 51 , 52 ]. [ 53 ] opined that the experience of consumers with technology application is a major element in measuring consumer satisfaction with products and services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Four types of uncertainties were identified as crucial factors influencing PR in the framework of MPS. Previous research works have analysed service quality (Ghotbabadi et al , 2016), privacy (Chen and Ha, 2019) and security (Natarajan et al , 2018) as the major antecedents of PR. But the present study makes a distinction by showcasing the sources of PR from an uncertainty viewpoint so as to comprehend the formulation of the risk perception among the consumers towards using MPS.…”
Section: Discussionmentioning
confidence: 99%